2013
DOI: 10.1080/09687599.2012.732536
|View full text |Cite
|
Sign up to set email alerts
|

‘It takes two to tango …’ revisited: a qualitative study on integration and participation of people living with spinal cord injury in Switzerland

Abstract: We aimed to examine how integration and participation are understood by persons with spinal cord injury. A qualitative study was carried out where we analysed 14 interviews with persons with spinal cord injury living in Switzerland. Integration was more often understood in terms of social acceptance and inclusion, while individual activities were more often highlighted in definitions of participation. Environmental factors were seen as the most important determinants. Applied strategies comprised pre-arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Friends were described as stabilisers and important supporters to maintain psychosocial wellbeing. Strong wishes to be independent, findings which are in line with several studies [ 29 33 ], and contribute within the family, socially and vocationally and at the same time not being a burden to family members or friends was expressed.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Friends were described as stabilisers and important supporters to maintain psychosocial wellbeing. Strong wishes to be independent, findings which are in line with several studies [ 29 33 ], and contribute within the family, socially and vocationally and at the same time not being a burden to family members or friends was expressed.…”
Section: Discussionsupporting
confidence: 71%
“…A study investigated applied strategies used by persons with SCI to function autonomously, such as planning and organizing, being assertive and asking for help and learning from peers with SCI [ 29 ]. Four studies explored how persons with disabilities in general [ 30 , 31 ] and SCI in particularly [ 32 , 33 ] conceptualized participation and integration, and found that key elements were accessibility, social support and social connection, experiencing personal growth and feeling validated. But a major challenge was barriers in society.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these difficulties, we suggest a new theoretical framework outlining the influence of EFs on participation, which can better address the complex interplay between EFs and disability. As an extension of the ICF framework (2), we hypothesize that experienced participation may impact on the intention to participate and on avoiding and overcoming behaviours (12). Our proposed new framework is illustrated in Fig.…”
Section: Development and Cognitive Testing Of The Nottwil Environmentmentioning
confidence: 99%
“…-Self-efficacy -belief in own ability 36 -Mental health and higher life satisfaction 41 -Client-centered rehabilitation 69,70,49 -Physical exercise enhances mental strength 42 -Lack of motivation, dissatisfaction, and depression after transition to home 18,39,47,49,58,70,71 -Lack of advanced intervention for depression, neuroticism, feeling of grief 41…”
Section: Resultsmentioning
confidence: 99%